Penerapan Media YouTube untuk Meningkatkan Kemampuan Pemahaman Matematis Siswa - Ari Septian; Erma Monariska; Eka Yunita (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to answer whether after applying YouTube media to mathematics learning can improve students' mathematical understanding skills in class X SMK PGRI 1 Tourism Cianjur. The research method used is a quasi-experimental method with the design form The Nonequivalent Pretest-Posttest Control Group Design. The population of this study were students of class X SMK PGRI 1 PariwisataCianjur. Involving a sample of 31 students from two classes selected through purposive sampling technique. Class X Banking as an experimental class and class X Catering as a control class. The instrument used is a test instrument in the form of a pretest and posttest to measure the ability of mathematical understanding and non-test in the form of an attitude scale questionnaire. Quantitative data analysis in this study uses SPSS 22. The results of the analysis show that increasing mathematical understanding skills by applying YouTube media is better than mathematical understanding skills using ordinary learning.